1997
DOI: 10.1080/02681219780001001
|View full text |Cite
|
Sign up to set email alerts
|

Atypical strains ofCandida albicansrecovered from AIDS patients

Abstract: By using multilocus enzyme electrophoresis (MLEE) we have analyzed the genetic diversity encountered among chlamydospore-positive Candida albicans strains. While the type II strains of the former C. stellatoidea were genetically indistinguishable from those of C. albicans, type I strains constituted a distinct subgroup compared with C. albicans strains. Nevertheless, all these strains remained genetically very closely related compared with other species of Candida (e.g.C. tropicalis, C. krusei and C. glabrata)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
48
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 32 publications
4
48
0
Order By: Relevance
“…The patterns of some type II C. stellatoidea isolates were indistinguishable from those of some C. albicans isolates, demonstrating a lack of species specificity or low resolving power, if one accepts C. stellatoidea as an independent species (170). It is more likely that C. stellatoidea type II represents a subgroup of C. albicans, as has been suggested (172,290). rDNA and mitochondrial DNA probes, therefore, have not been generally used in broad epidemiological studies of the infectious fungi, and neither method has been validated for the different levels of genetic resolution.…”
Section: Restriction Fragment Length Polymorphisms With Hybridizationmentioning
confidence: 99%
“…The patterns of some type II C. stellatoidea isolates were indistinguishable from those of some C. albicans isolates, demonstrating a lack of species specificity or low resolving power, if one accepts C. stellatoidea as an independent species (170). It is more likely that C. stellatoidea type II represents a subgroup of C. albicans, as has been suggested (172,290). rDNA and mitochondrial DNA probes, therefore, have not been generally used in broad epidemiological studies of the infectious fungi, and neither method has been validated for the different levels of genetic resolution.…”
Section: Restriction Fragment Length Polymorphisms With Hybridizationmentioning
confidence: 99%
“…Although the initial reports of atypical C. albicans isolates that proved to be C. dubliniensis (15,19,26) and many of the subsequent reports on this new species involved work done with isolates from HIV-positive patients (12,13,23,27), it is recognized that this species is not restricted to HIV-positive individuals (9,10,14,16,17). However, it has been generally accepted that C. dubliniensis preferentially colonizes HIV-positive individuals.…”
mentioning
confidence: 99%
“…Some authors have proposed that clonal propagation with a remaining capacity of recombination, shape the population structure of C. albicans (Caugant & Sandven 1993, Gräser et al 1996, Tibayrenc 1997. Pujol et al (1997) demonstrated that the fingerprinting of C. albicans randon amplified polymorphic DNA (RAPD), multilocus enzyme electrophoresis (MLEE) and Southern blot hybridization with the moderately repetitive DNA Ca3 probe, not only clustered moderately related isolates in a similar fashion but also afforded similar levels of resolution of microevolution within a clonal population.…”
mentioning
confidence: 99%